FOOD OF THE SARDINES, SARDINELLA ALBELLA (VAL.) AND S. GIBBOSA (BLEEK.) OF THE MANDAPAM AREA - Sekharan, K V (Indian Journal of Fisheries, 2011)
THAT heterogeneous feeding relationship (Ivlev, 1961) in a sardine may beassociated with the progressive development of gill rakers during ontogenyhas become evident from the studies on the food of the Pacific sardine,Sardinops caerulea (Scofield, 1934) and the Japanese sardine, Sardinopsmelanosticta (Tokai Regional Fisheries Research Laboratory, 1960). Thisaspect has been referred to by other workers also (Larraneta, 1960) but notyet studied properly. A closely related problem is selective feeding, theinvestigation of which requires simultaneous collections of plankton andsardine samples, as borne out by the studies of Hand and Berner (1959) onthe food of the Pacific sardine and of various workers on hsrxmg-Calanusrelationship (Gushing, 1955).